2015
DOI: 10.1002/cncr.29243
|View full text |Cite
|
Sign up to set email alerts
|

Flat epithelial atypia and risk of breast cancer: A Mayo cohort study

Abstract: Background Based on its cytologic features, and its co-occurrence with atypical hyperplasia and breast cancer, flat epithelial atypia (FEA) has been proposed as a precursor lesion on the pathway to breast cancer development. It is often referred to as an “atypical” or high-risk lesion. However, the long term risk of breast cancer in women with FEA is undefined. Methods Biopsies with FEA were identified in excisional breast biopsies in the Mayo Clinic Benign Breast Disease (BBD) Cohort, which includes 11,591 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(48 citation statements)
references
References 32 publications
3
45
0
Order By: Relevance
“…However, with the exception of atypical hyperplasia and very dense breasts, the risk associated with each of these factors is modest. Even the strongest risk factors of atypia (47, 48) and dense breasts (49) identify many women who will never develop breast cancer, leading to a search for molecular markers that would increase both the sensitivity and the specificity of present risk assessment methods.…”
Section: Discussionmentioning
confidence: 99%
“…However, with the exception of atypical hyperplasia and very dense breasts, the risk associated with each of these factors is modest. Even the strongest risk factors of atypia (47, 48) and dense breasts (49) identify many women who will never develop breast cancer, leading to a search for molecular markers that would increase both the sensitivity and the specificity of present risk assessment methods.…”
Section: Discussionmentioning
confidence: 99%
“…For the 31 patients in their study with FEA plus AH, the upgrade rate to DCIS or invasive cancer was 19.4%, and they recommended surgical excision. Lastly, Said et al examined the Mayo Clinic Benign Breast Disease Cohort from 1967 to 2001 and identified 282 patients with FEA . Of the 152 (54%) patients with pure FEA, the standardized incidence ratios (SIRs) for development of subsequent breast cancer were 2.04 (95% CI: 1.23‐3.19).…”
Section: Discussionmentioning
confidence: 99%
“…The counter argument is that the associated coexisting disease is relatively indolent and could be managed with surveillance. 810,16,17,19 In addition, the intrinsic biologic risk for future breast cancer is considerably lower for FEA than for ADH. 38 …”
Section: Discussionmentioning
confidence: 99%